Autonomy support in telehealth: an evolutionary concept analysis - Hou, Yi; Sun, Manyao; Huang, Xueying; Nan, Jiang; Gao, Jing; Zhu, Nan; Jiang, Yuyu (Frontiers in Public Health, 2025)
AimsAutonomy support plays a critical role in safeguarding patients’ fundamental rights and promoting health behaviors. The context of autonomy support is transitioning from traditional face-to-face healthcare settings to telehealth, leading to an evolution in the connotation of autonomy support. This study aimed to clarify the connotation of autonomy support in telehealth and to develop a conceptual framework to guide innovations in clinical practice and the advancement of related theories.MethodsRodgers’ evolutionary method was used to clarified attributes, antecedents, and consequences of autonomy support in telehealth. The integrative review strategy of Whittemore and Knafl was used as the methodology for searching relevant literature.ResultsTwenty-five articles were included. The attributes were identified as: (i) technical feedback; (ii) virtual agent; (iii) choice; (iv) rationale; (v) empathy; (vi) collaboration; and (vii) strengths. The antecedents were: (i) telehealth service system; (ii) change in awareness toward autonomy support; and (iii) patient preference of needs for autonomy. The consequences were: (i) multidimensional perception; (ii) emotional experience; (iii) health behavior; (iv) social relation; and (v) technological dependence.ConclusionThis study clarified the attributes, antecedents, and consequences of autonomy support in telehealth, developing and improving a conceptual framework for autonomy support. These findings will provide a theoretical foundation for developing technology-enabled autonomy support strategies in telehealth practice, better adapting to the emerging needs of patients in the context of the digital age.